Comparison of Nanoparticulate CpG Immunotherapy with and without Allergens in Rao‐Affected Horses. (September 2015) - Klier, J.; Geis, S.; Steuer, J.; Reese, S.; Fuchs, S.; Mueller, R.S.; Winter, G.; Gehlen, H.
Abstract : Reasons for performing study: New therapeutic strategies to modulate immune responses in human and equine allergic airway diseases are under extensive investigation. Stimulation of Treg cells with immune modulating agents is a novel therapeutic option. Objectives: The aim of this field study was to compare the effects of a nebulised nanoparticulate CpG immunotherapy (CpG‐GNP) with and without specific allergens. Study design: Longitudinal clinical study comparing 2 therapeutic options. Methods: Twenty RAO‐affected horses were divided into 2 treatment groups (CpG alone and CpG with allergens). Two specific allergens were selected for each horse according to anamnesis and a functional in vitro test. Treatments were given by nebulisation 7 times and the horses were examined 3 times: baseline (I), after the treatment course (II), and after 6 weeks later (III). Clinical parameters, indirect intrapleural measurement, arterial blood gas, amount of tracheal mucus and neutrophil percentage were evaluated. Results: CpG alone resulted in a significant improvement in clinical parameters and a significant reduction of tracheal mucus after treatment and at 6 weeks post treatment. After CpG plus specific allergens, there was significant improvement of 70% of examined parameters. However, there were no significant differences in the results compared with CpG‐GNP treatment alone. Conclusions: There were no significant differences between treatment groups. CpG‐GNP immunotherapy alone produced a potent and persistent effect on allergic and inflammatory parameters and may have potential as for treatment of equine and human allergic inflammatory airway diseases. Ethical animal research: The study was approved by the regional legal agency for animal experiments of the Government of Bavaria, Germany (No. 55.2‐1‐54‐2531‐31‐10). Owners gave informed consent for their horses' inclusion in the study.Sources of funding: Partly supported by the Deutsche Forschungsgemeinschaft (DFG) (Germany) (GE'2044/4‐1). The AeroNeb Go™ vibrating mesh nebuliser (Aerogen, Galway, Ireland) was sponsored by Inspiration Medical (Bochum, Germany).Competing interests: None declared.